MENGIDENTIFIKASI KENDALA DAN UPAYA GURU DALAM MEMPERTAHANKAN MUTU PEMBELAJARAN PENDIDIKAN AGAMA HINDU PADA MASA PANDEMI DI KOTA DENPASAR - Ni Komang Sutriyanti; I Made Luwih; I Dewa Gede Darma Permana (UHN IGB Sugriwa Denpasar, 2022)
Corona Virus Disease 2019 (COVID-19) pandemic has succeeded making education directed online (on the network). Online learning is as run as over time, raises several obstacles in the process of implementation. Reflecting on this, this study chose schools in the Denpasar city as a sample to identify obstacles during the online implementation. In this study, several problems were also formulated, namely related to the stage of implementing online learning in the Denpasar city during the pandemic, various obstacles faced, along with efforts to overcome them. The method used in this research was qualitative research types, with primary and secondary data sources. The technique of determining informants using purposive sampling techniques. The data collection methods used was using observation techniques, interviews, document recording, and literature studies, and analysing the data using Miles and Huberman. The results of this study shown that, some of the obstacles faced during online learning are obstacles in terms of cellphones, quotas and networks, as well as the delivery and receipt of subject matter. The efforts have been done were providing learning package books, giving assignments through offline, maximizing internet quota distribution and establishing more intensive communication and flexibility teaching schedules. Through this research, it is hoped that it will be able to maintain the learning quality of Hinduism eduation and Budi Pekerti (Character) because all obstacles are known and faced.